2010
DOI: 10.1653/024.093.0312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Life Cycle ofScyphophorus acupunctatus(Coleoptera: Curculionidae) Under Laboratory Conditions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The pupa is pale yellow, and later darkens as black pigment accumulates and the pupa turns black (Harris 1936). The pupal stage lasts 9 to 10 d. Developing wings are apparent on the dorsal side of the pupa, with the head, snout, eyes, and antennae on the ventral side (Valdés-Estrada et al 2010). The pupa measures 15 to 19 mm in length (Harris 1936).…”
Section: Pupamentioning
confidence: 99%
“…The pupa is pale yellow, and later darkens as black pigment accumulates and the pupa turns black (Harris 1936). The pupal stage lasts 9 to 10 d. Developing wings are apparent on the dorsal side of the pupa, with the head, snout, eyes, and antennae on the ventral side (Valdés-Estrada et al 2010). The pupa measures 15 to 19 mm in length (Harris 1936).…”
Section: Pupamentioning
confidence: 99%
“…The quality and quantity of food resources are known to contribute to intraspecific variability in the number of larval instars in insects (Esperk et al 2007), which may account for the difference between the 2 studies. Studies on other curculionids such as Rhynchophorus ferrugineus Olivier (Jaya et al 2000), C. sordidus (Gold et al 1999), and Scyphophorus acupunctatus Gyllenhal (Valdés-Estrada et al 2010) have also reported intraspecific variability in the number of larval instars in response to variation in nutrition.…”
Section: Head Capsule Width Is Useful For Determining Larval Instar Imentioning
confidence: 99%